How to realize the potential of soil carbon benefits? Practical pathways for acheiving impact - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Presented by Lini Wollenberg, CCAFS Low Emissions Development, at the GIZ expert meeting on Soil Carbon: Potentials recognized - but how to implement? on 28 April 2020.